A Prototype of a remotely controlled multichannel surface muscle stimulator - P. Silverio-Cevallos; J.; D. A. Molina-Vidal; C. J. Tierra-Criollo; P. Cevallos-Larrea (Ingenius: Revista de Ciencia y Tecnología)
Multichannel Functional Electrical Stimulation (FES) technology is widely employed in artificial motor control research. This study presents the design and evaluation of a four-channel, remotely controlled surface electrical muscle stimulator prototype. The prototype introduces a modern alternative for the control block, employing a Wi-Fi-enabled solution based on the ESP32 microcontroller. This controller enables remote configuration of activation sequences for individual channels and supports extensive customization of parameters for a biphasic waveform stimulus. The current signal is demultiplexed into four outputs. Additionally, this study provides a detailed functional evaluation of the amplification stage and examines the load-dependent limitations of the output current magnitude. Preliminary experimental testing demonstrates the prototype's ability to generate controlled stimulation sequences in hand muscles. The prototype's functional and experimental performance suggests its potential application in artificial motor control research.